METODE DAKWAH JAMAAH TABLIGH DI KERUNG-KERUNG KOTA MAKASSAR - Sulkarnain Nain Maidin (Jurnal Dakwah Tabligh, 2020)
This research is related to the Da'wah Tablig Strategy in Makassar City's Kerung-Kerung which aims to identify; (1) Da'wah Tablig method in the Makassar City Kerung-Kerung Region, (2) The effectiveness of the Da'wah Tablig method in the Makassar City Kerung-Kerung Region, (3) the opportunities and challenges of the Da'wah Tablig Region in the Makassar City Kerung-Kerung Region. The results showed that the propaganda method of Jamaah Tablig was divided into maqami practices consisting of the Deliberation Method, the Taklim Method, the Hospitality Method (Jaulah), and the intiqali practice in the form of Khuruj Fii Sabilillah (Rihlah Method). The presence of the Da'wah Tablig gave new inspiration for changes in the Kerung-Kerung region, making the community's economy grow rapidly and more prosperously marked by the swarming of traders around the mosque and became one of the trade centres in Kerung-Kerung in particular and in Makassar City in general. On the other side spiritually, the community can be influenced to come to the Jami Kerung-Kerung Mosque to participate in various Tablig Jamaah activities. The Da'wah Tablig also touches "special" communities such as thugs, gamblers and drug addicts. Although at first, it was undeniable that some people were not happy because of their ignorance of the Jama'at Tablig method of preaching. In addition, the challenges of the Da'wah Tablig mission also come from various problems in the family.